2012
DOI: 10.3346/jkms.2012.27.11.1347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Imaging Characteristics and Outcomes between Provoked and Unprovoked Acute Pulmonary Embolism in Koreans

Abstract: This study was performed to compare clinical and imaging parameters and prognosis of unprovoked pulmonary embolism (PE), provoked PE with reversible risk factors (provoked-rRF), and provoked PE with irreversible risk factors (provoked-iRF) in Koreans. Three hundred consecutive patients (mean age, 63.6 ± 15.0 yr; 42.8% male) diagnosed with acute PE were included. The patients were classified into 3 groups; unprovoked PE, provoked-rRF, and provoked-iRF; 43.7%, 14.7%, and 41.7%, respectively. We followed up the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…In Uhm et al's study, CRP >5 mg/L significantly correlated with poor long-term prognosis in unprovoked patients with PE. 25 While in Jeffrey's study, CRP did not demonstrate an excellent predictive value for RVD and long-term death. 69 Abul also drew a similar conclusion.…”
Section: Some Other Biomarkersmentioning
confidence: 80%
See 2 more Smart Citations
“…In Uhm et al's study, CRP >5 mg/L significantly correlated with poor long-term prognosis in unprovoked patients with PE. 25 While in Jeffrey's study, CRP did not demonstrate an excellent predictive value for RVD and long-term death. 69 Abul also drew a similar conclusion.…”
Section: Some Other Biomarkersmentioning
confidence: 80%
“…99 Uhm et al found that creatinine >1.2 mg/dL significantly correlated with poor longterm prognosis in unprovoked patients with PE. 25 Indicators of renal function correlated with PE severity, 98 and they are valuable in evaluating short-term 9,21,98,99 and long-term 25 prognosis. They have potential advantages in the assessment of PE severity, because they may reflect microcirculation dysfunction more sensitively than blood pressure.…”
Section: Some Other Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study from RIETE registry, they found that COPD patients presenting with PE have an increased risk for PE recurrence and fatal PE compared with those presenting with DVT alone and more efficient therapy is needed in this subtype of patients [29]. Uhm et al [30] from Korea performed to compare clinical and imaging parameters and prognosis of provoked and unprovoked acute PE patients and they found that provoked PE with irreversible risk factors has a poor prognosis for all-cause mortality and recurrent PE than unprovoked PE and provoked PE with reversible risk factors. Ellingsen et al [31] suggested that high RDW is a risk factor of incident VTE, and that RDW is a predictor of all-cause mortality in VTE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Eski bir biyobelirteç olmasına rağmen, PE'nın şiddetini yansıtıp yansıtmadığı halen bilinmiyor. Uhm ve ark'larının çalışmasında, CRP>5mg/L olması, kazanılmış risk faktörü bulunmayan PE'li hastalarda uzun dönem kötü bir prognostik faktör olduğu gösterilmiştir 73 . Ancak yapılan başka çalışmalarda, CRP'nin RVD ile uzun dönem mortalite arasında anlamlı bir ilişki tespit edilememiştir 74,75 .…”
Section: C-reaktif Protein (Crp)unclassified